Unraveling the Unique Role of Methyl Position on the Ring-Opening Barrier in Photocatalytic Decomposition of Xylene Isomers - Chen, Ruimin; Li, Jieyuan; Li, Xiaofang; Wang, Jielin; Taobo Huang; Liu, Wen; Dong, Fan (ACS Catalysis, 2022)
Photocatalytic efficiency toward volatile organic compounds (VOCs) decomposition has crucially relied on the nature of their stereochemical structures, in which the complicated decomposition mechanism has not been unveiled. As typical cases of VOCs pollutants, m-, p-, and o-xylene isomers share the identical molecular formula with discrepant methyl positions at the benzene ring. The essential contribution of the methyl position to the decomposition mechanism of xylene isomers, especially the rate-determining step for benzene ring-opening, is unraveled in this work. It is identified that the decomposition rate of xylene isomers on the SnO2 catalyst is decreased in the order of o-xylene > m-xylene ≈ p-xylene. The durability of SnO2 photocatalyst is also accomplished for a superior o-xylene decomposition performance. By combining the experimental and theoretical investigation, it is manifested that the regulation of methyl positions in the ortho-sites is an appealing route for reducing the ring-opening energy barriers and guiding the complete mineralization of the hazardous xylene. This work could provide insights into unraveling the unique role of the stereochemical structure of xylene on ring-opening barriers for efficient and stable VOC decomposition.